MENINGKATKAN HASIL BELAJAR IPS DENGAN MENGGUNAKAN PENDEKATAN COOPERATIVE LEARNING TIPE INSIDE OUTSIDE CIRCLE DI SD - Royani, Ida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
IPS learning in elememtary school still using conventional caused student learning outcome low, so the teacher will hold class action research that has goal to describe planning, application and evaluation by using Cooperative Learning Approach Inside Outside Circle type. By seeing the result of the research can be concluded that students learning outcome in cognitive domain will increase 17% , affective 12% and psychomotor 8% , so social science learning by using Cooperative Learning Approach Inside Outside Circle tipe must be applied and developed in order to increase the quality of education in the future. Kata Kunci : hasil belajar, pembelajaran IPS, cooperative learning tipe inside outside circle